Prevalence of ethical dilemmas in Slovenian family practice: Pogostnost etičnih dilem med zdravniki družinske medicine v Sloveniji - Klemenc-Ketiš, Zalika; Kersnik, Janko (Acta Medico-Biotechnica, 2022)
Purpose: To determine the perceived prevalence of ethical dilemmas in family practice. Methods: Self-administered questionnaire sent to a random sample of 259 Slovenian family physicians. The main outcome measure was the percentage of doctors reporting the frequency of ethical dilemmas on a 5-point scale.Results: Ethical dilemmas were common (mean score ± standard deviation, 36.2±12.5, out of a maximum of 100). The most common dilemmas involved decision-making regarding use of limited resources (23.9%), patient attempts to abuse the health care service (20.4%) and interfacing with the rest of the health care system (20.4%). Dealing with patients suspected of being physically abused, sexually abused, or involved in other violent acts was the least common ethical dilemma (
Keywords: bioethics; cross-sectional survey; prevalence; family practice; physician-patient relationship